Marginalised Writing Emerged and Focusing on the Identities of Ethnic Groups in India - G. N. Rohitkumar (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2024)
In the late 20th century, a political and social movement emerged to elevate the identities of ethnic groups like Tribes, Dalits, Women, and Peasants through marginalized writing. Tribal culture, the longest tradition in Indian culture, is reflected in ancient texts like The Ramayana and The Mahabharata. However, urbanization, print culture, and commerce have marginalized these groups and their languages, highlighting the need for more coordinated efforts to preserve and collect tribal languages and literature.